Detection and transit time measurements of individual sodium atoms diffusing in a helium flow by the laser resonance fluorescence correlation technique - Pan, Ci-Ling, author; She, C. Y., advisor (Colorado State University. Libraries, 1979)
This thesis describes the laser resonance fluorescence correlation technique for single-atom velocity measurement. Using this technique, we have detected individual sodium atoms diffusing through a laser beam in a slow helium flow. From the width of the fluorescence bursts detected, the transit time for the diffusing atom is determined. This is the first measurement of the motion of a single atom in a buffer gas. A probability analysis was developed which allowed us to estimate the average burst size of emitted fluorescence photons by an atom traversing the laser beam. All these results were in general agreement with the theoretical predictions. With improvements, we will be able to measure the velocity of a single-atom either in a flow or in a vacuum. By averaging over many sodium atoms, the diffusion coefficients of sodium atoms in helium and argon buffer gases were investigated using this technique. The measured diffusion coefficients were found to be in reasonable agreement with theoretical predictions and previous experimental results. To our knowledge, this is the first application of resonance fluorescence correlation technique to the measurement of diffusion coefficient of fast moving atoms in gases.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Atoms; Laser spectroscopy